Age at SARS-CoV-2 infection and psychological and physical recovery among Chinese health care workers with severe COVID-19 at 28 months after discharge: A cohort study - Li, Qian; Xiong, Lijuan; Cao, Xiongjing; Xiong, Huangguo; Zhang, Yanzhao; Fan, Yunzhou; Tang, Liang; Jin, Yang; Xia, Jiahong; Hu, Yu (Frontiers in Public Health, 2023)
Background No prior study had reported the psychological and physical recovery of patients with COVID-19 2~3 years after discharge from the hospital. Moreover, it is not clear whether there is any difference in the health status of the patients with COVID-19 of different ages after discharge from the hospital. Methods Embedding in the “Rehabilitation Care Project for Medical Staff Infected with COVID-19” in China, this study included 271 health care workers (HCWs) with severe COVID-19. Their status of health-related quality of life, persistent symptoms, functional fitness and immune function at 28 months after discharge were followed, and compared according to tertiles of age at SARS-CoV-2 infection (group of younger (≤ 33 years); medium (34-42 years); and older (≥43 years)). Multivariate linear regression and multivariable adjusted logistic regression models were applied in investigating the associations of age at SARS-CoV-2 infection and outcomes. Results At 28 months after discharge, 76% of the HCWs with severe COVID-19 had symptom of fatigue/weakness; 18.7% of the HCWs with severe COVID-19 did not fully recover their functional fitness; the decrease of CD3+ T cells, CD8+ T cells and the increase of natural killer cells accounted for 6.6, 6.6, and 5.5%, respectively. Compared with the HCWs with severe COVID-19 in younger group, HCWs with severe COVID-19 in older group had lower scores regarding physical functioning, role physical, bodily pain and role emotional; HCWs with severe COVID-19 in older group had higher risk of cough, joint pain, hearing loss and sleep disorder; HCWs with severe COVID-19 in older group scored lower on flexibility test. The variance of relative numbers of CD3+ T cells, CD8+ T cells and natural killer cells among HCWs with severe COVID-19 of different age groups were significant. Conclusions This study demonstrated that older HCWs with severe COVID-19 recovered slower than those with younger age regarding health-related quality of life, persistent symptoms, functional fitness and immune function at 28 months after discharge. Effective exercise interventions regarding flexibility should be performed timely to speed their rehabilitation, especially among those with older age.